The radiological case (Colombia Medica, 1990)
The patient was a young man who came to the Emergency Department of the Hospital Universitario del Valle, Cali, Colombia, with periumbilical colic pain and bilious vomiting. He had not passed stool or expelled flatus since 24 hours before admission. Deep palpation of the left hemiabdomen indicated pain. Fecal impaction was initially thought to be present. A new series of radiographs 12 hours later showed a radiological picture similar to that initially observed. The leukogram was normal. As the abdominal picture did not improve, an exploratory laparotomy was decided. The patient had no surgical history of any kind.